Production of high-affinity glycosylated anti-mouse conjugated nanobodies in Pichia pastoris - Orioli, Sofía; Santos, Javier; Ibañez, Lorena I.; D’Alessio, Cecilia (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionNanobodies (NBs) are small antibody fragments derived from camelid heavy-chain antibodies, which represent the minimal functional domain capable of antigen recognition and binding. NBs are 10 times smaller than conventional antibodies, exhibit a compact structure, and have high stability, making them ideal for recombinant production. The eukaryotic unicellular system Pichia pastoris provides multiple advantages for protein expression, including the ability to perform several eukaryotic post-translational modifications such as glycosylation.MethodsIn this work, we engineered a modular plasmid sequence that, through specific restriction enzyme cuts and ligations, codes the expression of a secreted anti-mouse kappa chain NB fused with various accessory peptides in P. pastoris. This system enables the incorporation of a plastic binding sequence for immobilization onto polystyrene surfaces, a histidine tag (Hisx6) for purification, the horseradish peroxidase (HRP) enzyme for chemiluminescence detection, or the biotinylatable AviTag sequence for detection using a different method, in multiple combinations.ResultsWe successfully expressed and purified anti-kappa NBs fused to a Hisx6-tag (κNB) and HRP–Hisx6-tag (κNB–HRP), with subsequent structural and functional characterization revealing high affinity and specificity for mouse immunoglobulins. The κNB–kappa light chain domain complex was modeled, showing a fitted surface interaction of the CDR3 domain. The position of a glycan present in κNB CDR3 within the complex was modeled, predicting that glycan addition would not affect the interaction surface. Accordingly, no functional differences were observed in κNB after deglycosylation, indicating that high mannose glycan addition has not interfered with its binding capability. Glycosylated and deglycosylated κNBs fused to HRP were produced with retained HRP activity and proved to be functional as secondary antibodies.DiscussionOur results show the P. pastoris eukaryotic system’s versatility in producing NBs and conjugated NBs with or without post-translational modifications that may be required for diverse biotechnological applications.